Personal and scientific reminiscences : tributes to Ahmed Zewail - Chergui, Majed; Rudolph A. Marcus; John Meurig Thomas (New Jersey : World Scientific, 2018)
'This book compiles a wonderful tribute to the late Ahmed H Zewail (1946-2016), considered the'father of femtochemistry' and a long-standing icon in the field of physical chemistry. Articles here are written by group of outstanding scientists from around the world who worked or have been affiliated with the Nobel prizewinning professor. Each article describes the authors own unique experience and relationship with Zewail, and includes details of scientific breakthroughs, discoveries, and the stories behind them. Personal and Scientific Reminiscences collects accounts from the most important individual in the physical and chemical sciences to give us a unique insight into the world and work of one of the great scientists of our time.'--
Keywords: Zewail, Ahmed H; Chemistry, Physical and theoretical; Chemists -- Egypt